2017
DOI: 10.15407/microbiolj79.03.125
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Soybean Mosaic Virus in Some Left-Bank Forest-Steppe Regions of Ukraine

Abstract: Soybean (Glycine max L.) is strategic legumes world crop of XXI century, which is located in the center of attention of world agricultural science and production. Soybean mosaic virus (SMV) is the most prevalent virus and is recognized as the most serious, long-standing problem in many soybean producing areas in the world. Infection by SMV usually results in severe yield losses, seed quality, seedling viability reduction of soybean. Study of soybean viruses in Ukraine were conducted exclusively on the Right Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…Симптоми ВСМП на рослинах пшениці озимої: а -фаза початку колосіння, ліворуч здорові, праворуч -хворі; б -сорт Смуглянка у фазі колосіння Обстеження рослин сої 25-ти сортів в умовах Полтавської області показали наявність симптомів зморшкуватості та мозаїки листової пластинки. Результати ІФА і ЗТ-ПЛР показали, що рослини інфіковані вірусом мозаїки сої [20]. Серед протестованих сортів нашу ува-гу привернув той факт, що вірусом мозаїки сої була уражена трансгенна соя Грімо, на якій спостерігали симптоми зморшкуватості й пухирчастості листкової пластинки (рис.…”
Section: а бunclassified
“…Симптоми ВСМП на рослинах пшениці озимої: а -фаза початку колосіння, ліворуч здорові, праворуч -хворі; б -сорт Смуглянка у фазі колосіння Обстеження рослин сої 25-ти сортів в умовах Полтавської області показали наявність симптомів зморшкуватості та мозаїки листової пластинки. Результати ІФА і ЗТ-ПЛР показали, що рослини інфіковані вірусом мозаїки сої [20]. Серед протестованих сортів нашу ува-гу привернув той факт, що вірусом мозаїки сої була уражена трансгенна соя Грімо, на якій спостерігали симптоми зморшкуватості й пухирчастості листкової пластинки (рис.…”
Section: а бunclassified
“…Noteworthy, Ukrainian SMV isolate Pol-17 which was earlier studied by us had some other phylogenetic relationships [27]. It indicates the differences between these Ukrainian SMV isolates.…”
Section: Resultsmentioning
confidence: 69%
“…Our previous studies of 30 soybean varieties in the Poltava region showed the presence of wrinkle and mosaic symptoms on leaves. The results of ELISA and RT-PCR showed that plants infected by Soybean mosaic virus (Mishchenko et al, 2017a). Among the inspected varieties, our attention was drawn to the fact that the SMV was affecting the transgenic varieties Monroe, Apollon and Grimo.…”
Section: Resultsmentioning
confidence: 99%